KETERATURAN PENIMBANGAN DENGAN PERTUMBUHAN ANAK BALITA - Ika Yuni Susanti; Sri Wardini Puji Lestari; Zulfa Rufaida (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2018)
Weighing the activities carried out in posyandu each once a month which aims to monitor the growth of infants and early detection of growth disorders. To achieve a small family, happy and sejahteraa undertaken by the family with the community with guidance from local health officials. This study aims to determine the relationship with the growth of infants weighing regularity in the Village District Gayaman, Mojoanyar, Mojokerto. The design used was an observational analytic type